Expression of Nutrient Transporters on NK Cells During Murine Cytomegalovirus Infection Is MyD88-Dependent - Khan, Abrar Ul Haq; Almutairi, Saeedah Musaed; Ali, Alaa Kassim; Salcedo, Rosalba; Stewart, C. Andrew; Wang, Lisheng; Lee, Seung-Hwan (Frontiers in Immunology, 2021)
Natural killer (NK) cells are the predominant innate lymphocytes that provide early defense against infections. In the inflammatory milieu, NK cells modify their metabolism to support high energy demands required for their proliferation, activation, and functional plasticity. This metabolic reprogramming is usually accompanied by the upregulation of nutrient transporter expression on the cell surface, leading to increased nutrient uptake required for intense proliferation. The interleukin-1 family members of inflammatory cytokines are critical in activating NK cells during infection; however, their underlying mechanism in NK cell metabolism is not fully elucidated. Previously, we have shown that IL-18 upregulates the expression of solute carrier transmembrane proteins and thereby induces a robust metabolic boost in NK cells. Unexpectedly, we found that IL-18 signaling is dispensable during viral infection in vivo, while the upregulation of nutrient transporters is primarily MyD88-dependent. NK cells from Myd88-/- mice displayed significantly reduced surface expression of nutrient receptors and mTOR activity during MCMV infection. We also identified that IL-33, another cytokine employing MyD88 signaling, induces the expression of nutrient transporters but requires a pre-exposure to IL-12. Moreover, signaling through the NK cell activating receptor, Ly49H, can also promote the expression of nutrient transporters. Collectively, our findings revealed multiple pathways that can induce the expression of nutrient transporters on NK cells while highlighting the imperative role of MyD88 in NK cell metabolism during infection.